2023
DOI: 10.1101/2023.04.01.534865
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Selective inhibition of OSBP blocks retrograde trafficking by inducing partial Golgi degradation

Abstract: Sterol-binding proteins are important regulators of lipid homeostasis and membrane integrity; however, the discovery of selective small molecule modulators can be challenging due to structural similarities in the sterol binding domains. We report the discovery of highly potent and selective inhibitors of oxysterol binding protein (OSBP), which we term oxybipins. Sterol-containing chemical chimeras aimed at identifying new sterol binding proteins by targeted degradation, led to a significant reduction in Golgi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
0
0
0
Order By: Relevance
“…In vitro fluorescence polarization assays with a recombinant glutathione S-transferase (GST)-tagged sterol-binding domain of OSBP (OSBP-related domain or ORD) 37 indicated that orpinolide engages OSBP in the nanomolar range and that binding is selective over other sterol transporters 38,39 (Fig. 4e and Extended Data Fig.…”
Section: Orpinolide (W7) Targets the Oxysterol-binding Protein Osbpmentioning
confidence: 99%
“…In vitro fluorescence polarization assays with a recombinant glutathione S-transferase (GST)-tagged sterol-binding domain of OSBP (OSBP-related domain or ORD) 37 indicated that orpinolide engages OSBP in the nanomolar range and that binding is selective over other sterol transporters 38,39 (Fig. 4e and Extended Data Fig.…”
Section: Orpinolide (W7) Targets the Oxysterol-binding Protein Osbpmentioning
confidence: 99%